Youth Soccer Lower Extremity Injuries Presenting to US Emergency Departments Are Decreasing: A 10-Year Analysis of National Injury Data - Alex G. Chun, B.S.; Eli M. Snyder, B.S.; Kyle K. Obana, M.D.; Beth G. Ashinsky, M.D., Ph.D.; Robert L. Parisien, M.D.; Thomas S. Bottiglieri, D.O.; Christopher S. Ahmad, M.D.; David P. Trofa, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To examine lower extremity youth soccer injuries presenting to US emergency departments. Methods: Data from the National Electronic Injury Surveillance System were analyzed for soccer players ≤18 years old sustaining lower extremity injuries from January 2013 to December 2022. Patient data collected included age, sex, mechanism of injury, setting (practice vs game), diagnosis, lower extremity injury, and disposition. Raw data were used to calculate national estimates (NEs) based on the assigned statistical sample weight of each hospital. Results: A total of 503,169 lower extremity injuries were diagnosed in US emergency departments (57.2% male; 42.8% female). On average, there was a decrease in 3,124 injuries per year from 2013 to 2022 (95% confidence interval, –5,324 to –925; P = .01) and 2,384 per year from 2013 to 2022 excluding 2020 (95% confidence interval, –3,452 to –1,315; P < .01). The ankle (NE = 196,592; 39.1%), knee (NE = 147,364; 29.3%), and foot (NE = 58,999; 11.7%) were the most commonly injured. The most common mechanisms of injury were not specified (NE = 188,653; 37.5%), ankle roll (NE = 71,992; 14.3%), and player-to-ground (NE = 581,90; 11.6%). The three most common diagnoses were strain/sprain (NE = 247,274; 49.1%), other/not stated (NE = 91,355; 18.2%), and contusion/abrasion (NE = 74,552; 14.8%). Conclusions: Youth lower extremity soccer injuries presenting to US emergency departments decreased from 2013 to 2022. Sex-specific analyses showed that there were significant differences in proportions of injuries between male and female participants for mechanism, diagnoses, and body parts injured. Clinical Relevance: This study provides insight into the epidemiology of lower extremity youth soccer injuries presenting to US emergency departments over a 10-year period.